Extracellular vesicles in chronic lymphocytic leukemia - Haderk, Franziska; Hanna, Bola; Richter, Karsten; Schnölzer, Martina; Zenz, Thorsten; Lichter, Peter; Seiffert, Martina (Leukemia and lymphoma, 2013)
Extracellular vesicles (EVs) are membrane-enclosed nanoparticles 30 to 1000 nm in size and represent a novel mechanism of cell communication. By transferring RNA and protein from their cell of origin, they can reprogram target cells and thus are involved in changes within the cellular microenvironment - a key player in CLL pathogenesis. In the current study, we were able to isolate EVs of 20 to 300 nm from blood plasma of CLL patients as well as from supernatant of primary CLL cells in culture. Further, proteomic profiling by Coomassie staining of SDS-PAGE gels and by mass spectrometry revealed an EV-specific protein profile. These findings suggest that EVs represent an important mean of CLL cells to interact with other cells, which might contribute to the establishment of a pro-survival microenvironment for CLL cells.